Fiscal Councils : Rationale and Effectiveness - Beetsma, Roel (IMF Working Papers; Working Paper ;, 2016)
The paper discusses the effectiveness of independent fiscal institutions-or fiscal councils-in taming the deficit bias that emerged in the 1970s. After a review of the main theoretical arguments and recent trends about fiscal councils, we develop a stylized model showing how a fiscal council can effectively mitigate the deficit bias even though it has no direct lever on the conduct of fiscal policy. We show that the capacity of the fiscal council to improve the public's understanding of the quality of fiscal policy contributes to better align voters and policymakers' incentives and to tame the deficit bias affecting well-intended governments. After mapping the model's key features into a broad set of criteria likely to contribute to the effectiveness of a fiscal council, we use the 2014 vintage of the IMF dataset on independent fiscal institutions to assess whether existing institutions have been built to work.